Anti-slip and wear resistance performance of three novel coatings as surface course of airstrip. Issue Volume 19:Issued 4(2018) (3rd April 2018) - Zhang, Jun; Weng, Xing-Zhong; Liu, Jun-Zhong; Yang, Bo-Han; Wen, Xiao-Ping; Wang, Tian
Abstract: Airstrip can be used to cater to the emergency need of an airport. For shortening construction time, the surface course should be handled as fast as possible. This paper explores the carboxylic styrene butadiene latex (CSBL), waterborne epoxy resin (WER) and modified polyurea elastomer (MPE) for any possibility to be used as surface course for an airstrip. The anti-slip test and the wear resistance test were performed to evaluate the coatings' anti-slip and wear resistance performance. Test results indicate that: (1) The British Pendulum Number (BPN) of stabilised and reinforced soils meets the specifications. The BPN increases with the increase of cement and fibre contents. Samples with surface course can meet the requirements of BPN in a dry state; however, the BPN is slightly lower than that of the requested value in a wet state. When the sand is added to the coatings, the BPN can meet the requirements and its value ranges between 36.8 and 49.9; and (2) Cement and fibre enhance the wear resistance performance of samples. The wear mass per unit area of stabilised soil is less than half of the plain soil. As the content of fibre increases from 0.3 to 0.8%, the wear mass per unit area decreases from 19.4 to 11.8 kg/m 2 as well as the wear depth decreases from 3.33 to 2.69 mm. The functional surface course can greatly enhance the performance of wear resistance. The enhancement of MPE can be regarded as the most significant. The addition of sand slightly improves the performance of wear resistance for CSBL and WER. The MPE can meet the requirements of anti-slip and wear resistance performance of airstrip's surface course.